Caracterização da modulação autonômica e do perfil funcional de pessoas com Distrofia Muscular de Duchenne - Silva, Talita Dias da [UNIFESP] (2016)
Among Muscular Dystrophies, Duchenne muscular dystrophy (DMD) is the most common genetic neuromuscular disease. Abnormal autonomic signaling is increasingly recognized as an important symptom in neuromuscular diseases, since the progressive degeneration and atrophy occur in both skeletal muscle and in the myocardium. Given this, it is important to evaluate the heart rate variability (HRV) of patients with DMD, which reflects the Autonomic Nervous System (ANS) activity on the sinus node. Objective: To characterize the autonomic modulation of people with Duchenne muscular dystrophy, compare the results with those of patients with DMD using beta-blockers (BB). We evaluated 90 adolescents, 30 with DMD, all boys, aged 11 and 18. To control group evaluated 30 with DMD using BB and 30 subjects with normal development, all matched for age and sex. For the assessment of functionality we applied Vignos scales, Motor Function Measure Scale (MFM) and Egen Klassifikation (EK). HRV analysis was made with the Polar ProTrainer 800CX with adolescents at rest spontaneously breathing for 25 minutes. The results showed that the autonomic impairment that individuals with DMD exhibit, promote reduction of RR intervals (mean RR), increased sympathetic (0V%) and parasympathetic reduction (% 2LV and 2UV%). It also decreases the complexity (Shannon Entropy) and fractal properties long term (?2). Therapy with beta-blockers act only in heart rate (HR) average, but not on the time elapsed between adjacent RR intervals, though the BB exert effect on the fractal properties in the long term (?2). In conclusion, the subjects with DMD show a reduction of parasympathetic tone and increased sympathetic. Moreover, BB therapy does not seem to influence the autonomic modulation.